Solar activity and mortality: a meta-analysis of six cities in the Eastern Mediterranean and Middle East - Madeleine Wissoker; Carolina Zilli Vieira; Souzana Achilleos; Barrak Alahmad; Maria Athanasiadou; Anastasia Paschalidou; Nikos Kalivitis; Evangelia Samoli; Petros Koutrakis; Annalisa Quattrocchi (Atmospheric Environment: X, 2025)
Background: Solar and geomagnetic activity have been linked to a multitude of impacts on human health including cardiovascular disease (CVD), and total non-accidental mortality. However, this has not been assessed in the Eastern Mediterranean Region or the Middle East. Our study aimed to assess the effects of short-term geomagnetic disturbances (GMD) on mortality in six locations across the Eastern Mediterranean and Middle East regions (Athens, Thessaloniki, Crete, Greece; Kuwait City, Kuwait; Limassol and Nicosia, Cyprus). Methods: We used a time series analysis adjusted for temperature and humidity over the period between 1997 and 2019 to estimate the effects of GMD (Kp index, sunspot number - SSN, plasma beta, and interplanetary magnetic field - IMF) on daily total non-accidental, CVD, and respiratory mortality, for each study area. We applied meta-analysis to estimate the pooled GMD mortality effect across all locations. Results: Our analysis included 664,427 deaths over the study period. Kp index was found to be significantly associated with total, CVD, and respiratory mortality. There was a 0.94 % (95 % CI: 0.019, 1.87) increase in total non-accidental mortality; a 0.63 % (95 % CI: 0.013, 1.25) increase in CVD mortality; and a 2.53 % (95 % CI: 0.36, 4.75) increase in respiratory mortality per IQR increase in Kp index (IQR = 15.63). However, solar activity parameters (SSN, Plasma beta, or IMF) were not statistically significantly associated with mortality. Conclusions: Our findings indicate an association between exposure to higher levels of Kp index and total non-accidental, CVD and respiratory mortality in the Eastern Mediterranean and Middle East Regions. The results warrant additional exploration to ascertain if variations in solar activity-driven human physiological dynamics may also be linked to other health consequences.